The influence of low-energy proton irradiaiton on threshold voltage and tranconductance of nanowire SOI n and p-channel transistors - Teixeira, Fernando F.; Agopian, Paula G. D. [UNESP]; Barraud, Sylvain; Vinet, Maud; Faynot, Olivier; Martino, Joao A.; IEEE (Ieee, 2017)
the goal of this work is analyze for the first time the low-energy proton irradiation effects on p and n- channel SOI Omega - Gate Nanowire transistors for total ionization dose of 500 krad. After radiation, it is noticed a slight variation on a drain current and in a transconductance, for large devices, due to the back leakage current.
Keywords: Nanowire; proton irradiation; back leakage current; oxide charger